⎩ ⎪ ⎨ ⎪ ⎧ x + y + z = 1 0 x 2 + y 2 + z 2 = 2 0 x 3 + y 3 + z 3 = 1 0 0
Consider three complex numbers x , y and z that satisfy the system of equations above. Find the value of x y z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's the proper and standard way to solve these type of questions. !!😀
We can use Girard's formula, x y z = 6 1 ( p 1 3 − 3 p 1 p 2 + 2 p 3 ) = 1 0 0 , where p k = x k + y k + z k
Sounds interesting. Where can I read more about Girard's formula? (Tried googling it but found no obvious links)
Log in to reply
These are usually called " Newton Sums " or "Newton Identities" in the Anglo-Saxon world, but the identity we are using here was know to Albert Girard long before Newton was born ;)
Squaring the first equation and subtracting second from it we get (xy+yz+zx)=40.
x
3
+
y
3
+
z
3
−
3
x
y
z
=
(
x
+
y
+
z
)
∗
{
x
2
+
y
2
+
z
2
−
(
x
y
+
y
z
+
z
x
)
}
.
Substituting the values from three equations and the one we found,
100 - 3xyz=10*(20-40), we get xyz=100.
Problem Loading...
Note Loading...
Set Loading...
→ x + y + z = 1 0 .... ( 1 )
→ x 2 + y 2 + z 2 = 2 0 .... ( 2 )
→ x 3 + y 3 + z 3 = 1 0 0 .... ( 3 )
Squaring both sides to ( 1 ) .
x 2 + y 2 + z 2 + 2 ( x y + y z + z x ) = 1 0 0
2 0 + 2 ( x y + y z + z x ) = 1 0 0
x y + y z + z x = 4 0
Adding ( − 3 x y z ) both sides to ( 3 ) .
x 3 + y 3 + z 3 − 3 x y z = 1 0 0 − 3 x y z
( x + y + z ) ( x 2 + y 2 + z 2 − ( x y + y z + z x ) ) = 1 0 0 − 3 x y z
1 0 × ( 2 0 − 4 0 ) = 1 0 0 − 3 x y z
x y z = − 3 − 3 0 0 = 1 0 0